Study on the Key Overlay Networking Techniques in vDC - Jiexin Zhang; Zhiming Wu; Wenhua Xu (Dianxin kexue)
The new demand from virtual data center was analyzed. Several key overlay SDN techniques that would be used for vDC interconnection were discussed, and several key problems of vDC interconnection should be focused were put forward.